082 The effects of poor maternal nutrition during gestation on the number of Pax7-positive myogenic progenitor cells. (1st August 2017) - Wynn, M. C.; Jones, A. K.; Hoffman, M. L.; Pillai, S. M.; McFadden, K. K.; Reed, S. A.; Zinn, S. A.; Govoni, K. E.
Abstract: Poor maternal nutrition during gestation can negatively affect fetal muscle development by altering the development of myogenic progenitor cells. We hypothesized that maternal nutrient restriction feeding and overfeeding during gestation would decrease the number of myogenic progenitor cells expressing the transcription factor paired box 7 (Pax7) in the LM of offspring. Pregnant western white-faced ewes ( n = 78) were fed 60, 100, or 140% of NRC requirements for TDN starting at d 30 ± 0.2 of gestation and offspring are referred to as RES, CON, and OVER, respectively. At d 45, 90, and 135 of gestation, ewes were euthanized for fetal muscle collection ( n = 10 to 15 fetuses per treatment per time point). Another group of ewes was allowed to undergo parturition, and lambs were necropsied within 24 h (birth; n = 10 to 13 per treatment). The LM was sampled from each fetus, cryosectioned (10 µm thickness), immunostained with Pax7 antibody and Hoechst (nuclei stain), and imaged ( n = 5 per fetus), and Pax7 positive [Pax7(+)] cells were quantified using ImageJ. Data were analyzed using PROC MIXED in SAS with main effects of maternal diet, litter size, and time point. An interaction of maternal diet × litter size ( P = 0.04) was observed such that within OVER offspring, the number of Pax7(+) cells in triplets was 72 and 67% greater compared with singletons and twins, respectively ( P ≤ 0.04). Between diets, the number of Pax7(+) cells was 76 and 49% greater in OVER triplets compared with CON and RES triplets, respectively ( P ≤ 0.03). No differences in the number of Pax7(+) cells were observed between litter sizes within RES and CON ( P ≥ 0.77) or within a litter size between CON and RES ( P ≥ 0.08). An interaction of time point × litter size was observed ( P = 0.04) such that at d 45, triplet offspring Pax7(+) cells were 24 and 45% greater compared with singletons and twins, respectively ( P ≤ 0.05). However, no differences in the number of Pax7(+) cells were observed between litter sizes at d 90 and 135 of gestation or birth ( P ≥ 0.16). In conclusion, triplets exhibit more Pax7(+) cells at early gestation and due to maternal overfeeding, which may delay their progression through myogenesis.